Prenatal Detection of Fetal Growth Restriction in Newborns Classified as Small for Gestational Age: Correlates and Risk of Neonatal Morbidity - Chauhan, Suneet P.; Beydoun, Hind; Chang, Eugene; Sandlin, Adam T.; Dahlke, Josh D.; Igwe, Elena; Magann, Everett F.; Anderson, Kristi R.; Abuhamad, Alfred Z.; Ananth, Cande V. (American Journal of Perinatology, 2014)
We examined the rate of detecting small for gestational age (SGA; birth weight < 10%) as intrauterine growth restriction (IUGR) prenatally at four centers and determined risks of composite neonatal morbidity (CNM) and mortality among detected versus undetected (no antenatal diagnosis of IUGR). A multicenter cohort study of 11,487 nonanomalous, singleton live births with sonographic exam before 22 weeks was performed. Of 11,487 births, 8% (n = 929) were SGA that met the inclusion criteria, with 25% of them being prenatally detected. The CNM among SGA births that were prenatally detected as IUGR was higher (23.3%) than undetected SGA (9.7%), but this difference was no longer significant following adjustments for confounding factors. Among preterm births (< 37 weeks), undetected SGA had significantly higher CNM (risk ratio [RR] 10.0, 95% confidence interval [CI] 6.3, 16.1) for deliveries at 24 to 33 weeks and RR 3.0, 95% CI 1.7, 5.4 for 34 to 36 weeks). In summary, only a quarter of SGA births were detected prenatally as IUGR and among preterm SGA, the CNM is significantly higher when SGA births are undetected as IUGR.
Keywords: small for gestational age; intrauterine growth restriction; composite neonatal morbidity; estimated fetal weight